Human personality and its survival of bodily death - Myers, F. W. H.; Johnson, Alice; Hodgson, Richard (Longmans, Green, 1903)
Long considered one of the most complete books dealing with psychical research. Myers treats all aspects of the mind which indicate, in some way, that the personality of man transcends time and space, and may perhaps survive bodily death.
Edited after the author's death by Richard Hodgson and Alice Johnson.
Includes bibliographical references and index (v. 2 for both volumes).
v. 1: 1. Introduction -- 2. Disintegrations of personality -- 3. Genius -- 4. Sleep -- 5. Hypnotism -- 6. Sensory automatism -- v. 2: 7. Phantasms of the dead -- 8. Motor automatism -- 9. Trance, possession and ecstasy -- 10. Epilogue.
Osler3485
Long considered one of the most complete books dealing with psychical research. Myers treats all aspects of the mind which indicate, in some way, that the personality of man transcends time and space, and may perhaps survive bodily death.
Keywords: Parapsychology / Research; Automatism; Spiritualism; Parapsychology; Immortality; Personality; Death; Association copies (Provenance) / rbprov / hou; Case Reports